2018
DOI: 10.1002/clc.22944
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural management of anticoagulation for atrial fibrillation catheter ablation in direct oral anticoagulant–treated patients

Abstract: Our data showed that uninterrupted DOAC therapy resulted in an unpredictable and highly variable initial level of anticoagulation before catheter ablation. Moreover, even with DOAC interruption preventing interference between DOAC, UFH, and ACT, intraprocedural UFH monitoring was complex. Altogether, our exploratory results call into question the appropriateness of transposing UFH dose protocols, as well as the relevance of ACT monitoring in uninterrupted DOAC-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 27 As has been described previously, there is individual variability in response to heparin that we do not fully understand. 12 As shown in Tables 2 and 3 , using the 139 dosing algorithm cases, we are beginning to understand factors that may contribute to this variability. A next step based on the modeling shown here will be to use a larger dataset to derive and test models for initial bolus and infusion rates that take into account sex and renal function in addition to anticoagulation type, weight, and baseline ACT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 As has been described previously, there is individual variability in response to heparin that we do not fully understand. 12 As shown in Tables 2 and 3 , using the 139 dosing algorithm cases, we are beginning to understand factors that may contribute to this variability. A next step based on the modeling shown here will be to use a larger dataset to derive and test models for initial bolus and infusion rates that take into account sex and renal function in addition to anticoagulation type, weight, and baseline ACT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated unpredictable and highly variable initial levels of anticoagulation using NOACs. 2 , 12 , 13 At the University of Wisconsin, an academic center in Madison, Wisconsin, with 5 electrophysiologists performing catheter ablation during the study period, heparin dosing was inconsistent between providers and required frequent nurse-physician interactions for dosing decisions. Others have reported on similar knowledge gaps in catheter ablation for AF: (1) difficulty achieving therapeutic ACT, especially with NOACs; (2) practice variation among individual providers; and (3) lack of protocols to deliver intraprocedural anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Martin, et al reported on periprocedural management of anticoagulation during CA-AF in patients treated with apixaban, dabigatran or rivaroxaban. 30 Patients received fixed doses of UFH ranging from 4,000 to 10,000 units corresponding to doses ranging from 38 to 110 units/kg based on actual body weight. Additional UFH doses to maintain an ACT ≥ 300 seconds were left to the discretion of the electrophysiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Uninterrupted DOAC results in a large and unpredictable range of concentrations and highly variable level of anticoagulation at baseline. 21 Alternatively, it is speculated that some DOAC such as apixaban may directly inhibit the level of FXa. 16 Finally, ACT values on DOAC vary according to the device used and to the drug itself.…”
Section: Discussionmentioning
confidence: 99%